GC-NICI-MS analysis of acetazolamide and other sulfonamide (R-SO2-NH2) drugs as pentafluorobenzyl derivatives [R-SO2-N(PFB)2] and quantification of pharmacological acetazolamide in human urine - Olga Begou; Kathrin Drabert; Georgios Theodoridis; Dimitrios Tsikas (Elsevier, 2020)
Acetazolamide (molecular mass (MM), 222) belongs to the class of sulfonamides (R-SO2-NH2) and is one of the strongest pharmacological inhibitors of carbonic anhydrase activity. Acetazolamide is excreted unchanged in the urine. Here, we report on the development, validation and biomedical application of a stable-isotope dilution GC-MS method for the reliable quantitative determination of acetazolamide in human urine. The method is based on evaporation to dryness of 50 μL urine aliquots, base-catalyzed derivatization of acetazolamide (d0-AZM) and its internal standard [acetylo-2H3]acetazolamide (d3-AZM) in 30 vol% pentafluorobenzyl (PFB) bromide in acetonitrile (60 min, 30 °C), reconstitution in toluene (200 μL) and injection of 1-μL aliquots. The negative-ion chemical ionization (NICI) mass spectra (methane) of the PFB derivatives contained several intense ions including [M]‒ at m/z 581 for d0-AZM and m/z 584 for d3-AZM, suggesting derivatization of their sulfonamide groups to form N,N-dipentafluorobenzyl derivatives (R-SO2-N(PFB)2), i.e., d0-AZM-(PFB)2 and d3-AZM-(PFB)2, respectively. Quantification was performed by selected-ion monitoring of m/z 581 and 83 for d0-AZM-(PFB)2 and m/z 584 and 86 for d3-AZM-(PFB)2. The limits of detection and quantitation of the method were determined to be 300 fmol (67 pg) and 1 μM of acetazolamide, respectively. Intra- and inter-assay precision and accuracy for acetazolamide in human urine samples in pharmacologically relevant concentration ranges were determined to be 0.3%-4.2% and 95.3%-109%, respectively. The method was applied to measure urinary acetazolamide excretion after ingestion of a 250 mg acetazolamide-containing tablet (Acemit®) by a healthy volunteer. Among other tested sulfonamide drugs, methazolamide (MM, 236) was also found to form a N,N-dipentafluorobenzyl derivative, whereas dorzolamide (MM, 324) was hardly detectable. No GC-MS peaks were obtained from the PFB bromide derivatization of hydrochlorothiazide (MM, 298), xipamide (MM, 355), indapamide and metholazone (MM, 366 each) or brinzolamide (MM, 384). We demonstrate for the first time that sulfonamide drugs can be derivatized with PFB bromide and quantitated by GC-MS. Sulfonamides with MM larger than 236 are likely to be derivatized by PFB bromide but to lack thermal stability. Keywords: Acetazolamide, Derivatization, Quantification, Sulfonamides, Validation